Comparison of the Psychological Symptoms and Disease-Specific Quality of Life between Early- and Typical-Onset Parkinson’s Disease Patients - Seyed-Mohammad Fereshtehnejad; Hasti Hadizadeh; Farzaneh Farhadi; Gholam Ali Shahidi; Ahmad Delbari; Johan Lökk (Parkinson's Disease)
The impact of Parkinson’s disease (PD) on psychological status and quality of life (QoL) may vary depending on age of disease onset. The aim of this study was to compare psychological symptoms and disease-specific QoL between early onset versus the rest of the PD patients. A total number of 140 PD patients with the mean current age of 61.3 (SD=10.4) yr were recruited in this study. PD patients with the onset age of ≤50 yr were defined as “early-onset” (EOPD) group (n=45), while the ones with >50 yr at the time of diagnosis were categorized as the “typical-onset” (TOPD) patients (n=95). Different questionnaires and scales were used for between-group comparisons including PDQ39, HADS (hospital anxiety and depression scale), FSS (fatigue severity scale), MNA (mininutritional assessment), and the UPDRS. Depression score was significantly higher in EOPD group (6.3 (SD=4.5) versus 4.5 (SD=4.2), P=0.02). Among different domains of QoL, emotion score was also significantly higher in the EOPD group (32.3 (SD=21.6) versus 24.4 (SD=22.7), P=0.05). Our findings showed more severe depression and more impaired emotional domain of QoL in early-onset PD patients. Depression and anxiety play an important role to worsen QoL among both EOPD and TOPD patients, while no interaction was observed in the efficacy of these two psychiatric symptoms and the onset age of PD patients.